Oncolytic influenza virus enhances killing effect of gemcitabine against pancreatic cancer cells - MENG Zihe; MENG Zihe; XU Yongru; DENG Zhaoda (陆军军医大学学报)
Objective‍　‍To investigate the killing effect of the recombinant oncolytic influenza virus OvFlu-GM-CSF， constructed using reverse genetics （RG） technology， in combination with chemotherapy drug， gemcitabine （GEM）， against pancreatic cancer cells. Methods‍　‍The recombinant oncolytic virus OvFlu-GM-CSF was successfully rescued using RG technology in our previous study. The virus was then comprehensively characterized through chicken red blood cell hemagglutination assay， transmission electron microscopy， and viral replication assay. CCK-8 assay was utilized to determine the impact of OvFlu-GM-CSF viruses ［multiplicities of infection （MOI）： 0， 0.1， 1.0， 3.0］ on the survival rate of pancreatic cancer cell lines （Panc02， PANC-1， SW1990， BxPC-3） and normal pancreatic ductal epithelial cells （HPDE6-C7） after treatment for 24， 48 or 72 h. Using a subcutaneous tumor-bearing mouse model of pancreatic cancer， 36 female C57BL/6 mice （6 weeks old） were randomly divided into PBS group， recombinant oncolytic virus group， GEM group， and the combined treatment group， with 9 mice in each group. PBS （100 μL/animal） or OvFlu-GM-CSF virus （1×107 PFU/100 μL） was given to the mice of the corresponding groups through intratumoral injection， while GEM （100 mg/kg） was injected intraperitoneally， once per 3 days， for totally 9 times. Changes in tumor volume and survival rate were monitored. Multi-immunofluorescence staining was employed to analyze T cell infiltration and proliferation in the tumor tissues. HE staining was performed to observe the pathological changes in major organs （heart， liver， lungs， kidneys and brain）， and the serum levels of alanine aminotransferase （ALT） and aspartate aminotransferase （AST） were measured to evaluate the safety of the recombinant oncolytic virus. Results‍　‍The recombinant oncolytic influenza virus OvFlu-GM-CSF has a hemagglutination titer of 28， typical morphological features of influenza virus， and can selectively replicate within pancreatic cancer cells. At the cellular level， the viruses demonstrated a significant selective cytotoxic effect on Panc02， PANC-1， SW1990， and BxPC-3 cells under the conditions of 48 h post-infection and MOI=3.0， when compared to 48 h post-infection and MOI=0 （P<0.01）. The cell survival rate was gradually decreased with the increase in MOI value and the extension of infection time （P<0.01）， but the viruses showed no significant effect on normal pancreatic ductal epithelial cells （HPDE6-C7）. In the pancreatic cancer tumor-bearing mouse model， the combined treatment of the viruses+GEM significantly reduced the tumor volume than simple virus treatment and simple GEM treatment （P<0.01）， and enhanced the infiltration of T cells in the tumor tissues. No obvious pathological changes were observed in the above-mentioned major organs. Additionally， there were no significant differences in the serum levels of ALT and AST in the OvFlu-GM-CSF group， GEM group， and OvFlu-GM-CSF+GEM group compared to the PBS group. Conclusion‍　‍RS technology-constructed recombinant oncolytic influenza virus OvFlu-GM-CSF， when combined with the chemotherapeutic agent GEM， enhances the cytotoxic efficacy against pancreatic cancer cells and effectively activates the host’s anti-tumor immune response. ［‍